Firearm access and adolescent suicide risk: toward a clearer understanding of effect size. Issue 3 (14th May 2020) - Swanson, Sonja A; Eyllon, Mara; Sheu, Yi-Han; Miller, Matthew
Abstract : Background: Strong and consistent associations between access to firearms and suicide have been found in ecologic and individual-level observational studies. For adolescents, a seminal case–control study estimated that living in a home with (vs without) a firearm was associated with a fourfold increase in the risk of death by suicide. Methods: We use data from a nationally representative study of 10 123 US adolescents aged 13–18 years to (1) measure how much adolescents who live in a home with a firearm differ from those who do not in ways related to their risk of suicide, and (2) incorporate these differences into an updated effect estimate of the risk of adolescent suicide attributable to living in a home with firearms. Results: Almost one-third (30.7%) of adolescents reported living in a home with firearms. Relative to those who did not, adolescents reporting living in a home with a firearm were slightly more likely to be male, older and reside in the South and rural areas, but few differences were identified for mental health characteristics. The effect size found by Brent and colleagues appeared robust to sources of possible residual confounding: updated relative risks remained above 4.0 across most sensitivity analyses and at least 3.1 in even the most conservative estimates. Conclusions: Although unmeasured confounding and other biases may nonetheless remain, our updated estimates reinforce the suggestion that adolescents' risk of suicide was increased threefold to fourfold if they had lived in homes with a firearm compared with if they had not.